STUDENTS’ PERCEPTION ON RUNNING DICTATION METHOD IN ESP CLASSROOM - Opik Dwi Indah (Institut Agama Islam Negeri Palopo, 2019)
This research is intended to find and describe students’ perception about running dictation in ESP classroom. Descriptive method is used of this research. To gain students’ perception about running dictation, the researcher used a questionnaire. The population of this research was the fifth semester students of Cokroaminoto Palopo University. The researcher applied purposive sampling technique and took 15 students as samples of this research. The results show that the students’ perception has advantages and also disadvantages towards running dictation method. The advantages namely: it can increase students’ vocabulary, practice students’ cooperation, practice students’ concentration and memory, and then make the learning process be more fun, interesting and not boring. Meanwhile, the disadvantages namely: it can make the students get injury and feel exhausted because of running. Therefore, based on their perceptions, in solving those problems, the researcher finds a new technique by changing the running becomes walking. This change will be called walking dictation method.